Testis on the move: a rare and elusive case of traumatic testicular displacement to groin - Saeed, Zabeena; P. Y., Prajna; Morang, J. P. (International Surgery Journal, 2025)
Testicular dislocation after blunt trauma to scrotum or to the abdomino-pelvic region is a rare entity, which happens due to spasm of cremasteric muscles. It can be unilateral or bilateral. It can go unnoticed on the first clinical examination at presentation because of associated injuries to other major organs. In this case report, we present the case of an adult male who presented with road traffic accident injury to the faciomaxillary region at some health institute but was later diagnosed with traumatic dislocation of right testis to groin. Later, he presented in our health facility where he was evaluated and diagnosed with traumatic dislocation of the testis of the right side. After confirming the clinical diagnosis of traumatic testicular dislocation with radiological examination, he underwent emergency surgical exploration of right testis and proceeded to orchiopexy. His post op period was uneventful and he was discharged on post op day second. On follow up, the patient did not have any urologic or sexual dysfunction on clinical examination and follow up radiological examination was also normal. Scrotal examination should be thoroughly done to avoid the delay in making the diagnosis of traumatic testicular dislocation. Although few cases can be managed conservatively with manual reduction, surgical exploration remains the mainstay so as to avoid the further complications later in life.